(untitled) (City: History, Culture, Society, 2026)
The article examines the history of the formation and development of the collection in Khmelnytskyi Regional Art Museum (KRAM) over 39 years of its existence amid continuous socio-political and cultural turbulence. The study traces the transformation of the museum from a Soviet-type art institution to the first state museum of contemporary Ukrainian art in independent Ukraine. Special attention is paid to the shift in collection-building concepts, the decisive role of museum professionals in shaping the acquisition strategy, and the main sources of collection growth, including state purchases, inter-museum exchanges, exhibition projects, art residencies, symposia, and donations from artists and private collectors. The article highlights the significance of KRAM as a representative platform for the study and museification of Ukrainian art processes of the twentieth and twenty-first centuries. It also analyzes the institutional modernization of the museum in the 2010s–2020s, focusing on digitalization, curatorial and educational practices, as well as the museum’s activities during the full-scale war as a socio-rehabilitative and cultural hub. The research demonstrates that a consistent strategic vision, openness to change, and a clear focus on contemporary Ukrainian art have ensured the museum’s institutional sustainability and professional authority.